Działania promocyjne i wizerunkowe szkół zawodowych z województwa podlaskiego – modele, narzędzia, skuteczność - Widelska, Urszula; Kowalczyk-Kroenke, Anna; Wiącek, Marta (Księgarnia Akademicka Publishing, 2025)
PROMOTIONAL AND IMAGE-BUILDING ACTIVITIES OF VOCATIONAL SCHOOLS IN THE PODLASKIE PROVINCE – MODELS, TOOLS, EFFECTIVENESS The monograph is the result of comprehensive research conducted by a team from the University of Lomza as part of the project KPO/22/LLL/U/0004 “Establishing a System for Coordinating and Monitoring Regional Actions for Vocational Education, Higher Education, and Lifelong Learning, including Adult Learning,” co-financed by the National Recovery and Resilience Plan (investment A.3.1.1). Its main objective is a multidimensional analysis of promotional and image-building activities undertaken by vocational schools in the Podlaskie Voivodeship. The authors focus on evaluating the effectiveness of communication tools used and their alignment with the needs and expectations of key stakeholders such as students, parents, teachers, and employers. The publication includes both theoretical aspects related to educational marketing and an extensive empirical section based on quantitative and qualitative research. The analysis covers, among others, the communication channels used by schools, mechanisms for shaping institutional image, the role of social media, and the determinants of effective educational communication. The final part of the monograph presents a model for promoting vocational education adapted to regional conditions.